2015
DOI: 10.5194/acp-15-11011-2015
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon, particle number concentration and nitrogen oxide emission factors of random in-use vehicles measured with the on-road chasing method

Abstract: Abstract. The chasing method was used in an on-road measurement campaign, and emission factors (EF) of black carbon (BC), particle number (PN) and nitrogen oxides (NOx) were determined for 139 individual vehicles of different types encountered on the roads. The aggregated results provide EFs for BC, NOx and PN for three vehicle categories: goods vehicles, gasoline and diesel passenger cars. This is the first on-road measurement study where BC EFs of numerous individual diesel cars were determined in real-world… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 28 publications
6
29
0
Order By: Relevance
“…For the CO 2 production rate, we adopted a value provided by the VTT Technical Research Centre of Finland, CMF CO 2 / CMF fuel = 3141 g (kg fuel) −1 , the same as used by Yli-Tuomi et al (2004). Similar values were reported in other papers like Ježek et al (2015). In order to characterize the fleet more representatively, 2 min averages were used in the emission factor calculations.…”
Section: Emission Factor Calculationsmentioning
confidence: 63%
See 1 more Smart Citation
“…For the CO 2 production rate, we adopted a value provided by the VTT Technical Research Centre of Finland, CMF CO 2 / CMF fuel = 3141 g (kg fuel) −1 , the same as used by Yli-Tuomi et al (2004). Similar values were reported in other papers like Ježek et al (2015). In order to characterize the fleet more representatively, 2 min averages were used in the emission factor calculations.…”
Section: Emission Factor Calculationsmentioning
confidence: 63%
“…Furthermore, the authors report that for the diesel passenger cars the relative amount of NO 2 increased as the NO 2 / NO x ratio was 10-15 % for Euro III and older type vehicles whereas it was 25-30 % for Euro IV-V type vehicles. Ježek et al (2015) observed reductions in the EF NO x for passenger cars and diesel heavy goods vehicles but no reduction for diesel passenger cars compared to those ten or more years old.…”
Section: Emission Factorsmentioning
confidence: 80%
“…Gentner et al, 2013;Liu et al, 2015;Ježek et al, 2015;Zavala et al, 2006;Jiang et al, 2005;Kristensson et al, 2004;Fraser et al, 1998;Miguel et al, 1998;Staehelin et al, 1998). These measurements provide a compositional overview of the exhaust emissions from the on-road vehicular fleet, consisting of a vast range of vehicle types (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Beijing, Wang et al (2011) found that approximately 5 % of the trucks are responsible for 50 % of the BC emissions. In Slovenia, a study of 139 individual vehicles of different types showed that 25 % of the highest-emitting diesel vehicles produce 63 % of the BC emissions (Ježek et al, 2015). Preble et al (2015) found that 20 % of trucks emit 80 % of the BC emissions from the Port of Oakland truck fleet (Preble et al, 2015).…”
Section: Superemittersmentioning
confidence: 99%
“…Using fuel-based emission factors from the EEA emission guidebook and NIIAT emission factors, BC emissions from on-road transport were estimated to be about 20.0 Gg (Evans et al, 2015). Similarly, Kholod and Evans (2016) use the Global Change Assessment Model (GCAM) to build a forecast for BC emissions from on-road transport in Russia. Total BC emissions from on-road transport were estimated to be about 20.0 Gg in 2015.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%